2023
DOI: 10.1186/s12887-023-04128-5
|View full text |Cite
|
Sign up to set email alerts
|

Association between Cesarean section and neurodevelopmental disorders in a Japanese birth cohort: the Japan Environment and Children’s Study

Abstract: Background The long-term effects of a Cesarean section (CS) birth on child neurodevelopment are of increasing interest. In this study, we examined the associations between mode of delivery and presence of neurodevelopmental disorders in toddlers. Moreover, given that the prevalence of several neurodevelopmental disorders such as autism spectrum disorder (ASD) is known to differ by sex, we also investigated these associations separately in male and female toddlers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…While previous studies have suggested an association between cesarean section and neurodevelopmental disorders 27 29 , a large Swedish cohort study in 2021 reported no association between cesarean section and abnormal neurological development 30 . This may be, in part, due to the many confounding factors expected to affect the child’s neurological developmental disorders, such as the reason for choosing a cesarean section, whether the cesarean section was an emergency or scheduled, and whether regional or general anesthesia was used.…”
Section: Discussionmentioning
confidence: 90%
“…While previous studies have suggested an association between cesarean section and neurodevelopmental disorders 27 29 , a large Swedish cohort study in 2021 reported no association between cesarean section and abnormal neurological development 30 . This may be, in part, due to the many confounding factors expected to affect the child’s neurological developmental disorders, such as the reason for choosing a cesarean section, whether the cesarean section was an emergency or scheduled, and whether regional or general anesthesia was used.…”
Section: Discussionmentioning
confidence: 90%